Sustainable Development Goal 4 and Women Empowerment in Ilorin West Local Government, Kwara-State, Nigeria - Ojo, Modupe; Osundina, Olasunkanmi (NIU Journal of Humanities, 2021)
The debate on the role of women in national development has been a discourse at the front burner of contemporary issues. This contention, to fast-track the empowerment of women necessitated the Sustainable Development Goals 4 to advance their inclusiveness in the polity for national development. However, a negation of the above in empowering women will result in devastating socio-economic life of a nation and by extension would affect development and personal fulfilment of individual in the community. The paper adopted survey research design. The targeted population were women of Ilorin-West local government area, Kwara State. A cluster sampling technique was adopted to divide respondents into multiple groups. Four Hundred (400) questionnaire were administered and three hundred and eighty one (381) were retrieved for analysis. Equally, secondary data were used to interrogate some salient and relevant issues. The paper found out that education has a role in improving the lives of women with attendant benefit to empower and promote gender parity in society. Paper also revealed that there are some key positions in the Ilorin West local government area that are exclusively men-based. However, final submission was that women in this local government area do have opportunities in certain fields of endeavour. In conclusion, paper recommends that since gender parity is important and the role of women central to socio-economic development, government should enact a policy to ensure quality education become a major block of empowering women at every local government area in Nigeria. Keywords: Women Empowerment, Ilorin-West, Quality Education, Sustainable Development and Kwara State